Catálogo sistemático de los coleópteros de la República Argentina. III - Carlos Bruch (Revista del Museo de La Plata)
Fam.PSELAPHIDAE Bythinoplectus Reitt. formicetorum Raffr. An. Mus. Nac. Bs. As., ser.  * Buenos Aires. 3a, t. XV, 1912, p. 443. Pselaphomorphus Motsch. Bruchi Raffr. Rev. Mus. La Plata, XV, 1908, p. 62.  * Buenos Aires. Jubus L. W. Schauf. elongatus (Schauf.) * Argentina,  Pam- Gamba elongata Schauf. Nunq. ot., II, 1872,         pas. p. 359. rugicollis (Schauf.) * Argentina, Pam- Gamba rugicollis Schauf. Nunq. ot., II, 1872,         pas. p. 360.